Hydrogenation of a,B-unsaturated carbonyl substrates by use of [Ir(COD)(PPh3)2] PF6 in 1-butyl-3-methylimidazolium hexafluorophosphate - López Linares, Francisco; Urdaneta, Johan; Sánchez, Victor; Sánchez Delgado, Roberto (Ciencia)
The biphasic selective hydrogenation a,b-unsaturated carbonyl substrates by use of (Ir(COD)(PPh3,)2,)PF6, in 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM)(PF6) is described and compared with the homogeneous system dissolved in pure toluene.